Fine mapping and identification of candidate pulmonary adenoma susceptibility 1 genes using advanced intercross lines - Wang, M.; Lemon, W.J.; Liu, G.; Wang, Y.; Iraqi, F.A.; Malkinson, Alvin M.; You, M. (2003)
In the present study, we used newly developed F11 generation mouse advanced intercross lines (AIL) to fine map Pas1–3 quantitative trait loci (QTL). The (A/J x C57BL/6) F11 AIL mouse population was created by crossing lung tumor-resistant C57BL/6 mice with lung tumor-susceptible A/J mice. By selectively genotyping 30% of the population, we have confirmed the Pas1 QTL and narrowed it to an interval of 1.0 cM or 1.3 Mb in the vicinity of the Kras2 gene. The Pas2 QTL was detected by both ANOVA and regression analysis but not by MapMaker EXP/QTL software. In addition, an interaction between the Pas1 and Pas2 QTLs was revealed. However, the Pas3 QTL was not confirmed in this study. It was either lost during the development of the AIL or too weak to be detected using AIL. The Pas1 locus is now sufficiently fine-mapped that candidate gene(s) for the Pas1 locus can be characterized by positional cloning. In this study, all 27 of the known or predicted genes located in the Pas1 candidate region were characterized as possible candidate Pas genes. Six genes were selected for additional analyses because of their relevant function in tumorigenesis or allelic changes between A/J and C57BL/6 mice. The Lrmp gene bears amino acid polymorphisms among various mouse strains that are highly correlated with the Pas1 allele status. The Pas1c1 gene (RIKEN Ak016641), encoding an intermediate filament tail domain-containing protein, produces alternatively spliced transcripts across inbred strains of mice, and its splicing pattern cosegregates with the Pas1 allele. The genetic and expression data support these two genes as strong candidates for the Pas1 locus. Of the other four genes (Eca39, RIKEN Ak015530, mHoj-1, and Krag), no functional polymorphisms or differential gene expression were found in Eca39, mHoj-1, and Krag between lung tumor-susceptible and -resistant strains. The Ak015530 carries an amino acid polymorphism, but this polymorphism does not cosegregate with mouse lung tumor susceptibility. Thus, these 4 genes are less likely candidates for the Pas1 locus.